Elimination of cusps in dimension 4 and its applications. Issue 5 (4th October 2016) - Behrens, Stefan; Hayano, Kenta
Abstract : We study a class of homotopies between maps from 4‐manifolds to surfaces which we call cusp merges . These homotopies naturally appear in the uniqueness problems for certain pictorial descriptions of 4‐manifolds derived from maps to the 2‐sphere (for example, broken Lefschetz fibrations, wrinkled fibrations, or Morse 2‐functions). Our main results provide a classification of cusp merge homotopies in terms of suitably framed curves in the source manifold, as well as a fairly explicit description of a parallel transport diffeomorphism associated to a cusp merge homotopy. The latter is the key ingredient in understanding how the aforementioned pictorial descriptions change under homotopies involving cusp merges. We apply our methods to the uniqueness problem of surface diagrams of 4‐manifolds and describe algorithms to obtain surface diagrams for total spaces of (achiral) Lefschetz fibrations and 4‐manifolds of the formM × S 1, whereM is a 3‐manifold. Along the way we provide extensive background material about maps to surfaces and homotopies thereof and develop a theory of parallel transport that generalizes the use of gradient flows in Morse theory.